Implementasi E-Assessment dalam Pembelajaran Teks Ceramah Berbasis Culturally Responsive Teaching di Pondok Pesantren Modern Islam Assalaam - Rumiyanto, Hedonal; Huda, Miftakhul; Sufanti, Main (Universitas Muhammadiyah Surakarta, 2024)
The urgency of implementing Culturally Responsive Teaching (CRT) and E-Assessment in sermon text learning lies in the need to enhance the relevance of teaching materials to the cultural and religious backgrounds of students while providing more objective and efficient assessments. This study aims to analyze the effectiveness of combining CRT and E-Assessment in improving students' competencies at Pondok Pesantren Modern Islam Assalaam, particularly in sermon text learning. The study employed a qualitative approach with an embedded case study design. Data were collected through in-depth interviews, participatory observations, documentation, and audio-video recordings. Thematic analysis was conducted to identify patterns in teaching and technology-based assessment practices. The results show that CRT enhances the relevance of learning materials to students’ cultural contexts, boosting confidence, participation, and intercultural understanding. Meanwhile, E-Assessment provides a more objective and efficient tool for evaluating sermon texts, particularly in terms of structure, coherence, and language use. However, the study also highlights challenges, such as limitations in assessing the performative aspects of speaking skills and the need for more inclusive material development. The study concludes that the combination of CRT and E-Assessment is effective in supporting students' competency development, although further innovations are needed in technology integration and teacher-student training.